Pendampingan Orang Tua Siswa Melalui Penyusunan Media Alat Hitung Manual (ALHIMA) dalam Mendampingi Anak Belajar dari Rumah Selama Masa Pandemi Covid-19 - Silviana Nurfaizah; Ummu Khairiyah; Winarto Eka Wahyudi; Mudzaki Risma (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
The implementation of online learning under the Minister of Education and Culture Circular No. 4 of 2020 during the Covid-19 pandemic caused new problems. 76% of 25 parents in grade I primary schools in Sugihrejo village had difficulty assisting children in learning numeracy material. Training on the preparation of manual counting media (ALHIMA) is an absolute effort to improve the quality of parent learning assistance on numeracy material. By using the service-learning method, this service is proven to be able to improve the quality of parent learning assistance on numeracy material which is characterized by new skills that parents have, including knowing the importance of using learning media, mastering the concept of addition and subtraction, using ALHIMA media for assistance in learning counting material, and being aware of the importance of providing the best assistance for children's academic success.